1998
DOI: 10.1097/00005344-199800001-00109
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Arterial Lesions in Dogs Treated With an Endothelin Receptor Antagonist

Abstract: Structurally and pharmacologically diverse vasodilators are known to lower blood pressure, increase heart rate, and produce acute injury to right coronary arteries in the dog. Administration of low concentrations of endothelin-1 (ET-1) to anesthetized dogs causes coronary vasoconstriction and reductions in coronary blood flow. Therefore, pharmacologic blockade of endothelin receptors (ETA and ETB) with the mixed ET receptor antagonist SB 209670 could lead to coronary vasodilatation. In toxicology studies, cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 4 publications
2
12
0
Order By: Relevance
“…Medial smooth muscle cell necrosis was associated with disorganisation or disruption of their basal laminae and those of adjacent cells that also displayed various lucent and dense cytoplasmic inclusions and separation of plasmalemmae from their basal laminae. The observed colocalisation of focal internal elastic lamina damage and medial injury is indicative of a mechanical basis for injury as has been observed following exposure to other vasoactive drugs and implicated as a primary factor in lesion pathogenesis (20,25). Disruption or breaks in the internal elastic lamina were observed in several of our studies.…”
Section: Physiological Assessmentssupporting
confidence: 82%
See 2 more Smart Citations
“…Medial smooth muscle cell necrosis was associated with disorganisation or disruption of their basal laminae and those of adjacent cells that also displayed various lucent and dense cytoplasmic inclusions and separation of plasmalemmae from their basal laminae. The observed colocalisation of focal internal elastic lamina damage and medial injury is indicative of a mechanical basis for injury as has been observed following exposure to other vasoactive drugs and implicated as a primary factor in lesion pathogenesis (20,25). Disruption or breaks in the internal elastic lamina were observed in several of our studies.…”
Section: Physiological Assessmentssupporting
confidence: 82%
“…Animals of the same sex and dose group were housed together in controlled environment rooms (15)(16)(17)(18)(19)(20)(21)(22)(23)(24) • C temperature and 40-70% relative humidity) and given 12 hours light/dark illumination. All animals were offered 400 g/day of irradiated SDS Dog Diet A [E] SQC (Special Diet Services, Witham, Essex, UK) and drinking quality tap water ad libitum.…”
Section: Animal Maintenancementioning
confidence: 99%
See 1 more Smart Citation
“…Medial degeneration and necrosis, adventitial edema, and variable inflammation, can also be associated with chronic proliferative phase of PDE III induced coronary arterial damage (22). Arterial changes induced by PDE III inhibitors are limited in distribution to coronary arteries in which both right and 26 CLEMO ET AL TOXICOLOGIC PATHOLOGY (33), theobromine (11), adrenergic inotropes (isoproterenol, norepinephrine, and dopamine) (41), and various types of endothelin receptor antagonists (2,31,47,49), have been reported to induce, in coronary arteries of dogs, an acute lesion that is morphologically similar to that described for PDE III inhibitors. Administration of CI-1020, an endothelin A receptor antagonist, resulted in medial smooth muscle necrosis and hemorrhage of extramural coronary arteries in dogs treated with single to multiple intravenous doses ( Figure 1a) (2).…”
Section: Vasoactive Induced Arterial Lesions In the Dogmentioning
confidence: 99%
“…The absence of changes in coronary blood ow may be related to the short duration of this study. Previous studies (10,11,22) with endothelin antagonists (ET A or ET A/ B ) have shown treatment-related vasodilation of coronary arteries as early as 3 hours posttreatment and minor but sustained decreases in mean arterial blood pressure in with prolonged (5-day) treatment.…”
Section: Endothelin-1 Levelsmentioning
confidence: 99%